Relinking of curricular areas and fields in preparation for the schooling of preschool girls and boys in Chihuahua - Sosa Padrón, Aliety; Marín Uribe, Rigoberto (IE Revista de Investigación Educativa de la REDIECH, 2021)
The transition from preschool to primary school represents an unprecedent experience for preschool girls and boys. In this journey, it is important to prepare girls and boys to enter primary school, as a formal, regulated space. Preparation for schooling in its current definitions establishes cognitive and socio-emotional learning that allows girls and boy to adapt to the new school. For this reason, in the present investigation, the training of preschool children is defined from a profile of expected learning linked to fields and curricular areas, from a complex and transdisciplinary approach. For this purpose, the study is covered by action research in its action-training-research variant, so that preschool and primary school teachers become researchers who reflect on their teaching practice.